Seasonal variation of residual flow in the east sea - Manh, Dinh Van; Yanagi, Tetsuo (Vietnam Journal of Mechanics, 2003)
A diagnostic three-dimensional numerical model has been established in order to reveal the seasonal variation of residual flow, including wind-driven current, density-driven current and tide-induced residual current, in the East Sea. The observed data on water temperature, salinity (from JODC, 1930-1996) and wind (from GOADS, 1961-1991) were exploited in this study. Residual flows in 4 seasons (spring, summer, autumn and winter) were simulated. Furthermore, the contribution of each component, wind-driven, density-driven and tide-induced residual current, was evaluated. On the basis of the obtained results, it is shown that the wind-driven current plays an important role in the basin-wide circulation in the East Sea, especially in the surface layer. At the lower levels, the density-driven current becomes more significant. The tide-induced residual current is relatively small.